Antecedents of Muslim Students' Decisions to Use Islamic Digital Banks - Qulub, Ana Fidatul; Ayuningtyas Putri, Rizky Nur (Universitas Dian Nuswantoro Semarang, 2024)
The primary objective of this research is to examine the many elements that influence the decision-making process of Muslim students when it comes to utilizing Islamic digital banking services. This study explains the Theory of Planned Behavior (TPB), specifically focusing on the constructs of attitude, subjective norm, and perceived behavioral control, in addition to supplementary exogenous variables, digital marketing, brand image, and digital financial literacy, and the intention to use. This research uses a quantitative Structural Equation Model (SEM) approach. The data collection technique used questionnaires distributed online to respondents, namely Muslim students who live in Solo Raya, and a total of 384 respondents participated. The findings indicated that each exogenous variable exhibited a statistically significant impact on the intention to use; Intention to use proved influential in Muslim students' decision to use Islamic digital banks. Perceived behavioral control, brand image, and digital financial literacy significantly affect Muslim students' decision to use Islamic digital banks. In contrast, attitudes, subjective norms, and digital marketing are not substantial on the decision of Muslim students to use Islamic digital banks. Intention mediates the indirect influence of exogenous variables on Muslim students' decisions to use Islamic digital banks.Keywords:Islamic Digital Banks, Muslim Students’ Decisions, Intention to Use, Attitude, Subjective Norm, Perceived Behavioral Control, Digital Marketing, Brand Image, Digital Financial Literacy